Traveling solutions and evolution properties of the higher order Camassa–Holm equation. (March 2017) - Ding, Danping
Abstract: This paper investigates general mild traveling solutions and the stationary solution of the higher-order Camassa–Holm equation. By argument of regularity and conservation, we construct admitted traveling solutions of the second order and the third order Camassa–Holm equations. Furthermore, evolution procedure and evolution properties of a traveling solution are discussed; the discussion reveals the periodic behavior of the traveling solution curve itself and its curvature. These investigations are valuable to understand forming and evolution of a pattern.